Loss of biliverdin reductase‐a (BVR‐A) impairs beneficial effects of CNS insulin on brain energy metabolism favoring the development of Alzheimer's disease (AD) neuropathology: Impact of CNS insulin signaling in Alzheimer's disease. (7th December 2020) - Lanzillotta, Chiara; Tramutola, Antonella; Di Domenico, Fabio; Vasavda, Chirag; Paul, Bindu D.; Snyder, Solomon; Butterfield, D. Allan; Perluigi, Marzia; Duarte, Joao M.N.; Barone, Eugenio
Abstract: Background: Alterations of brain insulin signalling are a common pathophysiological mechanism leading to dementia in AD and Type 2‐Diabetes Mellitus (T2DM). These alterations are often associated with mitochondrial stress, failure of energy metabolism, synaptic loss and ultimately neurodegeneration. Studies from our group identified impairment of BVR‐A – a regulator of insulin signalling – as an early event leading to insulin resistance in the brain. Here, we tested the hypothesis that reduced BVR‐A levels link failure of insulin signalling with mitochondrial stress resulting in AD neuropathology. Method: Alterations of insulin signalling pathways, autophagic flux, total oxidative stress levels and AD neuropathology were analyzed in the hippocampus of 6‐month old wild‐type and the goto‐kakizaki (GK) model of T2DM rats. Hippocampal mitochondrial function was evaluated by measuring oxygen consumption rate (OCR), mitochondrial complexes, mitochondrial unfolded protein response (UPRmt) and oxidative stress levels. These data were correlated with peripheral metabolic measurements (fasting glucose, insulin and OGTT) and cognitive tasks (spatial memory). To confirm the role of BVR‐A, similar analyses were performed in the hippocampus of 2‐ and 6‐month old BVR‐A knock‐out mice. Additional mechanistic insights were gained by evaluating the response to insulin in Sh‐Sy5y cells lacking BVR‐A. Results: GK rats displayed a diabetic phenotype and impaired spatial memory. Reduced BVR‐A levels along with IRS1 hyper‐activation and loss of Akt‐mediated inhibition of GSK3β were observed in the hippocampus, consistent with a regulatory role for BVR‐A. As result, hyperactive GSK3β accumulated in hippocampal mitochondria fostering their impairment characterized by reduced OCR and activation of UPRmt. Notwithstanding, reduced oxidative stress and pTau levels were observed in GK rats. BVR‐A KO mice displayed alterations of insulin signaling and mitochondrial function resembling those of GK rats with increased oxidative stress and pTau levels the adult mice. Loss of BVR‐A promoted an early protective response (UPRmt‐mediated) followed by a later general impairment (GSK3b‐mediated mitochondrial dysfunction, increased oxidative stress and pTau levels) in Sh‐Sy5y cells treated with insulin. Conclusion: These results suggest that early BVR‐A loss impairs brain insulin signalling favoring mitochondrial stress mediated by hyper‐active GSK3β. These alterations lead to impaired energy metabolism and development of AD neuropathology.